Gap Analysis Of The Quality Of Outstanding Services That Influence Patient Satisfaction - Riada Marenny Pasaribu (PT Inovasi Pratama Internasional, 2022)
This paper was aimed to identify factors the gap of quality service of outpatient that affect expectation of consumer in Outpatient Unit or Instalasi Rawat Jalan at Fatmawati General Hospital. this research uses post-poitivis approach and qualitative method to identify the factors analysis of quality service that affect expectation of consumer in Fatmawati General Hospital Outpatient by considering service quality by provider perspective (Gap 1-4). Service quality of gap 1-4 theory by Valerie Zeithaml, Leonard Berry, and Parasuraman (1990) is used to support the factors analysis. In fact, the expectation of consumer affected by quality service that has been delivered by provider. The indeks of consumer expectation has decreased through three years, it implies that there are obstacles of quality service must provider face. The quality service that has been delivered dosen’t fit and propper to consumer needs. discussion result of this research show some factual of service quality obstacles i.e research of management, infeasibility perception, performance measurement, technology job-fit,communication eksternal media, and gap between management expectation and consumer expectation